Recent Advances in Autism Spectrum Disorders Volume II - Fitzgerald, Michael (IntechOpen, 2013)
The pace of research on Autism Spectrum Disorders (ASD) has expanded exponentially in recent years. It is difficult for anyone to keep up with all developments. This book will assist the experienced and non-specialist reader to keep up with recent developments. The book opens with a focus on the evolutionary aspects of autism and then focuses on the public's attitude towards autism including the stigma issue. Then there is a focus on cortical modularity and electrophysiology followed by treatment issues including sensory, medical and community-based interventions. Finally, forensic issues are dealt with and the importance of the built environment is focused on. The book will be relevant to psychiatrists, psychologists, paediatricians, social workers, speech and language therapists, occupational therapists and care workers.